839. EUTREMA JAPONICUM: Brassicaceae. (September 2016) - Iwashina, Tsukasa
Summary: Eutrema japonicum (Miq.) Koidz. (syn. Wasabia japonica (Miq.) Matsum.) the rhizomes of which are known as the herb wasabi in Japanese restaurants, is described and illustrated. Its distribution, chemistry and cultivation are also discussed. A description of the genus Eutrema R. Br. is given, and the second Japanese species E . tenue (Miq.) Makino is illustrated.